Sexual violence among college students in East Java: patterns, gender perspectives, and implications for prevention - Winingsih, Evi; Nursalim, Mochammad; Habsy, Bakhrudin All; Billa, Nur Amanah (Jurnal Konseling dan Pendidikan, 2024)
Sexual violence among university students is a critical issue that demands serious attention, especially in the East Java region. This study aims to explore the prevalence, patterns, and gender perspectives of sexual violence while offering recommendations for prevention efforts. Using a quantitative approach with a cross-sectional survey design, data were collected from 155 undergraduate students from various universities in East Java, selected through random assignment. A sexual violence instrument measured verbal, physical, sexual, and emotional abuse. Descriptive statistical analysis was employed to examine the data. The findings reveal that 56.8% of respondents reported experiencing sexual violence, while 43.2% did not. Verbal abuse emerged as the most prevalent form of violence (40.6%), followed by emotional abuse (32.9%), unwanted sexual behavior (20.6%), and physical abuse (20%). Gender-based analysis highlighted distinct patterns: female respondents reported higher rates of verbal abuse (43.4%) compared to males (26.9%), whereas male respondents experienced more physical abuse (30.8%) than females (17.8%). The study also suggests potential underreporting and a lack of awareness regarding certain forms of sexual violence. These findings underscore the urgent need for gender education, awareness campaigns, and campus policies that foster safe and inclusive environments. Collaboration among educational institutions, government bodies, and communities is essential to design evidence-based interventions to prevent sexual violence among university students.